2018
DOI: 10.1245/s10434-018-6583-6
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Breast-Conserving Surgery for Multiple Ipsilateral Breast Cancer: An Initial Report from ACOSOG Z11102 (Alliance) Trial

Abstract: NCT01556243.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Multicentric cancer, previously thought to necessitate mastectomy, can be safely managed with breast-conserving surgery if two or more lumpectomies can be done with satisfactory cosmetic outcomes. 69 The widespread use of systemic therapy contributed to the reduction of locoregional recurrence. 70 Rates of locoregional recurrence after breast-conserving surgery followed by radiotherapy are approximately 2-3% at 10 years for ER-positive and HER2-positive tumours and 5% for TNBC, and do not differ significantly from those seen after mastectomy.…”
Section: Early Breast Cancer: Locoregional Therapymentioning
confidence: 99%
“…Multicentric cancer, previously thought to necessitate mastectomy, can be safely managed with breast-conserving surgery if two or more lumpectomies can be done with satisfactory cosmetic outcomes. 69 The widespread use of systemic therapy contributed to the reduction of locoregional recurrence. 70 Rates of locoregional recurrence after breast-conserving surgery followed by radiotherapy are approximately 2-3% at 10 years for ER-positive and HER2-positive tumours and 5% for TNBC, and do not differ significantly from those seen after mastectomy.…”
Section: Early Breast Cancer: Locoregional Therapymentioning
confidence: 99%
“…If there are two lesions very far apart in different quadrants, separate lumpectomies could be performed with clear margins, followed by radiation [3]. Patients should be made aware of an approximately 30% chance of positive margins requiring margin re-excision; however, the chance of conversion to mastectomy due to positive margins is only around 7% [4]. This particular patient was highly motivated to avoid mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The recent ongoing American College of Surgeons Oncology Group (ACOSOG) Z11102 prospective singlearm trial demonstrated in its initial results that 67.6% of the women that underwent BCS for MSIBC successfully completed surgery with negative margins, and with an acceptably low rate of conversion to mastectomy (7.1%). Also, it did not identify any specific patient, imaging or tumor factors that predict patients at increased risk for failure of BCS in the MSIBC population [51]. This study only enrolled patients eligible for BCS and not for mastectomy; however, the SENOMAC study is an ongoing trial that similarly to the Z11102 protocol enroll patients eligible for mastectomy.…”
Section: Breast Surgerymentioning
confidence: 99%
“…The results of trials in progress will enrich our knowledge and provide a sound scientific background for future management guidelines. The final data of ACOSOG Z11102, currently examining LRR following BCS for women with MSIBC [51] and the British MIAMI trial will evaluate the safety of oncoplastic procedures (BCS associated with mammoplasty) in MSIBC [45]. However, the limitation of this study enrolled only 50 patients.…”
Section: Breast Surgerymentioning
confidence: 99%